Irrigation cost recovery in developing countries - Abu-Zeid M. (Etat de l'agriculture en Méditerranée : Ressources en eau : développement et gestion dans les pays méditerranéens, 1993)
The cost of delivering irrigation water to agricultural producers in a marketing economy is customarily accomplished by private irrigation companies or districts that operate on a non-profit basis for the purpose of providing the service and the commodity at cost. In developing countries where the economy is usually subsided recovering the cost of water delivery is much more complicated and difficult. A key policy for cost recovery for an irrigation system should be based upon a sense of equity among the beneficiaries. Because costs for maintenance and operation lag seriously over years of operation, water is not usually delivered effectively and therefore produces inequities. Methods of assessment and collection of fees must be considered in light of country's economic and technical environment. This and other issue are discussed to assist decision/policy makers concerned with cost recovery.
Development and Management in Mediterranean Countries, 1992/09/03-09, Adana (Turkey)